An Ecological Cosmological Study of the Actions of Pandawara Group and Kalangsari Pride: A Structure of Spiritual Solidarity Between Humans and Nature - Wawaysadhya Wawaysadhya; Shofiyah Nurmasari; Isti Nur Faizah; Dian Ananda Permata (UIN Siber Syekh Nurjati Cirebon, 2025)
In recent decades, humanity has absorbed vast amounts of information concerning ecological and cosmological contexts of the human–nature relationship, alongside a growing awareness that human actions have contributed significantly to the disruption of planetary balance and sustainability. At the same time, humans live in deep interconnection with their environment, shaping unique identities and meanings in life.This study aims to develop a holistic understanding of the spiritual relationship between humans and nature. It also serves as a philosophical contemplation on the solidarity between humanity and the universe. Methodologically, this research employs a structured combination of quantitative and qualitative approaches, utilizing interpretive and inductive data analysis techniques, along with holistic and heuristic philosophical frameworks. To strengthen empirical grounding, field studies were conducted on the environmental actions of the Pandawara Group, representing grassroots ecological resistance, and the ecological rituals and expressions of Kalangsari Pride, which embody local cosmological awareness. Findings reveal that both communities have cultivated a tangible ecological-cosmological consciousness in their activities: Kalangsari Pride roots its environmental preservation efforts in local spirituality, while the Pandawara Group develops digital-based ecological activism focusing on youth education and interregional influence. Their actions demonstrate that social solidarity with nature can emerge through spiritual narratives and community collaboration. Furthermore, local perspectives—particularly those of community leaders—reflect an acknowledgment of the eco-spiritual values promoted by these groups. This study affirms the need for a holistic approach that integrates spiritual, educational, and collective dimensions to achieve sustainable environmental conservation.